LEGAL LIABILITY OF ACUPUNCTURE THERAPIST FOR PATIENT SAFETY INCIDENTS IN TRADITIONAL MEDICINE SERVICES REVIEWED BY HEALTH WORKERS LAW AND REGULATION OF THE MINISTER OF HEALTH ABOUT CONCERNING LICENSING AND IMPLEMENTATION OF ACUPUNCTURE THERAPIST PRACTICES - Isabella Dwinantya Chandra; Veronica Komalawati (Jurnal Poros Hukum Padjadjaran, 2023)
Traditional medicine services are one of the treatments and treatment efforts other than medical science and / or nursing science which is carried out by traditional health workers. Acupuncturists are skilled traditional healers who perform invasive procedures on patients that can cause patient safety incidents or potentially result in injury to the patient. But in fact, if there is a loss due to an error in treatment, the client / patient and / or the client / patient's family do not know the legal consequences for the acupuncturist who provides their therapist services. The purpose of this study is to gain a comprehension of acupuncture therapist authority on the medical service and to acquire a description of acupuncture therapist responsibility on patient safety incident on the medical treatment. This research article was carried out using normative juridical methods with secondary data through literature studies which were analyzed qualitatively. The results showed that the authority of the acupuncture therapist as a traditional skilled health worker was in accordance with the standard of expertise and skills as evidenced by STPT and SIPT. If a patient safety incident occurs due to an error in medical practice, it means that the acupuncturist has committed an illegal act and is responsible for paying compensation to the patient and / or the patient's family.